The Influence Of Usability Of The Wondr Application by BNI On User Satisfaction - Perdana, Imam Bintang; Hidayat, Rahmat Rian; Marwati, Arum (Jurnal Ilmiah Multimedia dan Komunikasi, 2025)
Wondr is a digital innovation developed by Bank Negara Indonesia (BNI) aimed at the younger generation through a mobile-first, interactive, and lifestyle-based design approach. However, during its initial launch, the application received numerous user complaints regarding frequent errors, which negatively affected its rating. This raises the question of how usability influences user satisfaction. This study aims to analyze the effect of usability of the Wondr by BNI application on user satisfaction, with a focus on active university students in the Special Region of Yogyakarta. The research employed a quantitative approach using a survey method involving 100 respondents determined through the Yamane formula. The usability variable was measured based on Quesenberyâ€™s indicators, namely effective, efficient, engaging, error tolerant, and easy to learn. Data were analyzed using validity and reliability tests, descriptive statistics, and simple linear regression with IBM SPSS Statistics 30. The findings indicate that the usability of the Wondr application falls into the â€œGoodâ€ category, while user satisfaction is also categorized as â€œGoodâ€. Regression analysis demonstrates that usability has a positive and significant effect on user satisfaction, with a significance value of < 0.001 and a coefficient of determination (RÂ²) of 0.529. Based on these results, it is recommended that BNI, as the developer, enhance the quality of onboarding and user guidance, particularly for new users. Future research on this topic is advised to adopt a broader approach, such as mixed methods or qualitative designs, to gain deeper insights into usersâ€™ subjective experiences.